Do Higher Wages Cause Inflation? - Magnus Jonsson; Stefan Palmqvist (Sveriges Riksbank, 2004)
Much empirical evidence suggests that wage increases do not lead to inflation. This paper demonstrates that a 2-sector dynamic general equilibrium model calibrated to the U.S. economy is able to explain this evidence. We quantify the effect of an increased wage-markup on the inflation rate in both the goods sector and the service sector. The mechanisms we emphasize and quantify are changes in relative prices and monetary policy. We find that our model is successful in explaining the empirical evidence. Quantitatively, the relative price effect is more important than monetary policy in mitigating the effect of higher wage-markups.
Keywords: D43; E31; E52; 330; Wage-markups; Relative prices; Monetary policy